"Why does feng shui have an appeal to the Filipino society?" - Directo, Mary Rosalynn L.; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Feng shui